Analisis Materi Buku Ajar Pelajaran Bahasa Arab di Madrasah Aliyah dari Perspektif Pedagogi Kritis - Afif Amrullah (Taqdir, 2021)
This research assumes that textbooks contribute to forming students' attitudes and behavior towards the realities that occurred around them. The discussion in this research is formulated interrogatively as follows: 1) How are textbooks considered from a critical pedagogical point of view? 2) What are the advantages and disadvantages of textbooks from the perspective of critical pedagogy? This research is of the type of library research whose analysis is based on a critical pedagogy perspective. In order to facilitate the data analysis process, this research uses the technique of critical discourse analysis. As for writing this research, it is presented in a descriptive and narrative form. This research concludes with the following results: 1) Textbooks do not reach students with low economic levels. 2) No questions in composition and spelling formats 3) The multiple choices exercise was very controlling 4) The textbooks contain many Islamic subjects; 5) The topic in the textbooks did not yet discuss issues around: capitalism, liberalism, secularism, gender equality and other major humanitarian themes.